Zdravljenje bolečine pri bolnikih z rakom - Lopuh, Mateja (Rehabilitacija (Ljubljana), 2008)
Pain is a feared complication of cancer with the vast majority of patients assuming that they will suffer from pain at some point in their disease. A systematic review of pain suggests that the prevalence of pain in all cancer patients is high, over 50%. One third of the patients evaluated their pain as moderate to severe. The mainstay of pain treatment are analgesic drugs, used by the principles of WHO analgesic ladder. Their effect can be more pronounced by using other drugs such as NSAR, anxiolytic drugs, antidepressants and anticonvulsive drugs. The drugs can be taken orally but there are other routes available. Physical modalities include TENS, acupuncture, massage and psycological support. Whenever possible, specific oncologic as well as surgical treatment is included. Successful pain treatment demands careful assessment of pain, finding the reason for it, knowing the possibilities available and regular evaluation of the treatment. The article discusses the analgesic treatment of pain in cancer patients. Drugs that can be used, indications and guidelines for their posology are presented. The basic principles of opioid titration, of calculating the breakthrough dose and opioid rotation are discussed. Guidelines for differential use of opioids are shown.
Keywords: bolečina; neželeni učinki; opioidi; rak (medicina); zdravila; zdravljenje